2023
DOI: 10.1159/000533481
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Biomarker for Vessel-Associated Retinal Diseases

Merlin Dähmcke,
Martin Busch,
Johanna M. Pfeil
et al.

Abstract: Introduction: Vessel-associated retinal diseases are a major cause of blindness and severe visual impairment. The identification of appropriate biomarkers is of great importance to better anticipate disease progression and establish more targeted treatment options. MicroRNAs (miRNAs) are short, single-stranded, non-coding ribonucleic acids that are involved in the post-transcriptional regulation of gene expression through hybridization with messenger RNA. The expression of certain miRNAs can be different in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Several recent reports highlighted the role of miRNAs on DR progression (Table 3) [194][195][196]. It was demonstrated that miR-15a, produced by pancreatic β-cells, increased in plasma EVs from diabetic patients and were related with retinal injury.…”
Section: Mirna On Dr Pathogenesismentioning
confidence: 99%
“…Several recent reports highlighted the role of miRNAs on DR progression (Table 3) [194][195][196]. It was demonstrated that miR-15a, produced by pancreatic β-cells, increased in plasma EVs from diabetic patients and were related with retinal injury.…”
Section: Mirna On Dr Pathogenesismentioning
confidence: 99%